In commemoration of the 70-th anniversary of the member of the Academy of Agricultural Science - Victor Fedorovich Pivovarov - O.N. Pishnaya; L.K. Gurkina; T.S. Naumenko; M.M. Tareeva (Овощи России, 2012)
On the 18th April of 2012 Pivovarov Victor Fedorovich - Director of the All-Russian Research Institute of Vegetable Breeding and Seed Production, Academician of Russian Academy of Agricultural Sciences, Honored Scientist of Russian Federation, State Laureate of Science and Technology, Doctor of Agricultural Science, Professor, is celebrating his 70-th Birthday and 48 years of his scientific and pedagogical activity. Dr. Pivovarov V.F. is the leading scientist in the field of ecology, introduction, horticulture, breeding and seed production of vegetable crops. Dr. Pivovarov V.F. is well-experienced in the field of solution of theoretical and practical problems. V.F. Pivovarov has founded the scientific school of the ecological breeding of vegetables with the complex resistance to biotic and abiotic stresses.